Autonomous homeostatis disturbances and peripheral circulation in adolescents with hypertensive neurocirculatory dystonia - S. N. Ivanov (Российский кардиологический журнал, 2005)
Correlation between peripheral circulation (PC) disturbances and autonomous regulation of heart function was examined in young men with hypertensive neurocirculatory dystonia (HNCD). The study involved 141 young males, aged 16-21, including 111 individuals with HNCD and 20 healthy participants. Rhythmocardiography method, including cardiointervalography and correlative rhythmography, was used. For PC assessment, upper extremity rheography was performed. Vessel tonus index (VTI), and volume blood flow rate (VBFR) were calculated. In controls, normotensive CP type was registered more often than in HNCD participants; sympathicotonic CP type was observed in HNCP individuals only. Autonomous support (AS) of heart function in HNSD patients was decreased, or provided by sympathic autonomous nervous system.